An investigation into the starting salaries of male and female veterinarians - Weiss, Jane Frances, author; Frasier, Marshall, advisor; Hadrich, Joleen, advisor; Koontz, Stephen, committee member; Jensen, Wayne, committee member (Colorado State University. Libraries, 2017)
Historically, the United States veterinary industry has been a male-dominated field, but in recent years women have surpassed men in veterinary school enrollment and now make up 60% of practicing veterinarians. There is evidence of a persistent gap between the starting salaries of male and female veterinary school graduates. This research investigates the effect of factors previously used to explain this gap and explores other factors that could further explain the unexplained residual gap heretofore attributed to wage discrimination. Most studies of wage gap attribute any unexplained residual from their statistical models as being the result of gender discrimination. However, most have not quantified or analyzed the effect of inherent differences between males and females, which could explain more of the unexplained portion instead of simple attribution toward systematic gender bias. Analysis of survey data of graduating veterinary medicine students reveals that the wage differential between the aggregate means of men and women is largely explained by employment self-selection, driven by what sectors the male and female graduates are choosing as their beginning employment within the veterinary field. However, much is still left unexplained. This study quantifies fundamental differences in the effect of male and female attributes through the regression techniques including ordinary lease squares and matching methods to analyze factors that explain the wage gap. The three-step methodology starts from an examination of the wage gap at the mean through the least squares models and then refines the resolution of analysis to identify that the wage gap is actually larger than originally estimated when comparing individuals with the same demographic factors through nearest neighbor matching. From this analysis, the fundamental differences between starting male and female veterinarians provide insight as to why the wage gap exists.
Keywords: graduating veterinarians; OLS; nearest neighbor matching; gender wage gap